Author Correction: The impact of poor asthma control among asthma patients treated with inhaled corticosteroids plus long-acting β2-agonists in the United Kingdom: a cross-sectional analysis. (December 2017) - Pavord, Ian; Mathieson, Nicola; Scowcroft, Anna; Pedersini, Riccardo; Isherwood, Gina; Price, David
A correction to this article has been published and is linked from the HTML version of this article.